Linguistic Politeness in Apologies: Comparing Strategies of Bruneian and Indonesian University Students - Zainuddin, Noor Amalia Nabilah; Yaqin, Lalu Nurul (Journal of Language and Literature Studies, 2024)
Linguistic politeness, especially in apology situations, is essential for maintaining social harmony and ensuring effective communication across different cultural contexts. The study aimed to examine linguistic politeness among university students in the context of apologies. The study compared politeness strategies between Bruneian and Indonesian university students from different universities. Data were collected using the Discourse Completion Task (DCT) method, where respondents were presented with specific situations or scenarios and asked to express what they would say in those situations. The data was analysed using the politeness model by Brown and Levinson (1987). The study found that students used positive politeness strategies, negative politeness strategies, and bald-on-record strategies. The study’s results show that positive politeness strategies are the most frequently used. The results also indicated that in using politeness in apologies, students employed several sub-strategies, such as greetings, promising, providing reasons, taking responsibility, understanding the interlocutor’s desires, and using titles for interlocutors with higher social status. This research can serve as a guide and lesson for improving linguistic politeness among university students, especially when apologising.